2015
DOI: 10.15376/biores.10.2.3314-3325
|View full text |Cite
|
Sign up to set email alerts
|

Non-Contact Detection of Surface Quality of Knot Defects on Eucalypt Veneers by Near Infrared Spectroscopy Coupled with Soft Independent Modeling of Class Analogy

Abstract: A knot is a natural defect that degrades the quality of softwood and hardwood veneer. To improve efficiency, the plywood industry needs a rapid, inexpensive method of knot identification that is easy to operate and industrialize. Although a non-contact knot-detection technology based on NIR spectroscopy and soft independent modeling of class analogy (SIMCA) has been successful in detecting softwood knots, it has not yet been explored in eucalypt (hardwood) veneer. This study investigated the interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The knot samples were found to have higher absorption amplitude than normal samples for each wood species. These changes in spectra were consistent with previous experiments by and Yang et al (2015Yang et al ( , 2016. This may be due to the difference in the orientation of the microfibrils within fibers between knots and normal wood, as the microfibrils of a knot's cells was substantially parallel to the NIR light incidence angle Yang et al 2015).…”
Section: Overview Of Spectrasupporting
confidence: 90%
See 2 more Smart Citations
“…The knot samples were found to have higher absorption amplitude than normal samples for each wood species. These changes in spectra were consistent with previous experiments by and Yang et al (2015Yang et al ( , 2016. This may be due to the difference in the orientation of the microfibrils within fibers between knots and normal wood, as the microfibrils of a knot's cells was substantially parallel to the NIR light incidence angle Yang et al 2015).…”
Section: Overview Of Spectrasupporting
confidence: 90%
“…The absorbance near 1195 nm was bound up with the second overtone of C-H stretching vibration from lignin or cellulose (Schwanninger et al 2011). The strong peak at approximately 1462 nm was primarily attributed to the O-H stretching from water or phenolic groups of lignin (Schwanninger et al 2011;Yang et al 2015).…”
Section: Overview Of Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, the ability of NIR spectroscopy coupled with SIMCA was investigated to detect the surface quality of knots detected on eucalypt veneers and results showed that the method had a classification accuracy of 94.4% for knot samples and 100% accuracy for knot-free samples (Yang et al 2015). In the present study, PLS-DA was selected for analyzing the data from NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 96%